2021
DOI: 10.1111/iej.13489
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the reporting quality of randomized trials within Endodontics using the Preferred Reporting Items for RAndomized Trials in Endodontics (PRIRATE) 2020 quality standard checklist

Abstract: Aim To critically evaluate the reporting quality of a random sample of clinical trials published in Endodontics against the PRIRATE 2020 checklist and to analyse the association between the quality of reported trials and a variety of parameters. Methodology Fifty randomized clinical trials relating to Endodontics were randomly selected from the PubMed database from 2015 to 2019 and evaluated by two independent reviewers. For each trial, a score of ‘1’ was awarded when it fully reported each item in the PRIRATE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 37 publications
1
24
1
Order By: Relevance
“…As such, efforts have been endorsed to improve and optimize conduct and reporting standards of RCTs (Moher et al, 2010), probably more than any other design of original research. The Preferred Reporting Items for RAndomized Trials in Endodontics (PRIRATE) 2020 guidelines have been developed exclusively for Endodontics following a standard consensus process (Nagendrababu et al, 2020a), in an attempt to improve reporting standards and minimize bias within the specialty (Nagendrababu et al, 2020b(Nagendrababu et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…As such, efforts have been endorsed to improve and optimize conduct and reporting standards of RCTs (Moher et al, 2010), probably more than any other design of original research. The Preferred Reporting Items for RAndomized Trials in Endodontics (PRIRATE) 2020 guidelines have been developed exclusively for Endodontics following a standard consensus process (Nagendrababu et al, 2020a), in an attempt to improve reporting standards and minimize bias within the specialty (Nagendrababu et al, 2020b(Nagendrababu et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…RCTs complying with the PRIRATE 2020 guidelines [ 88 , 89 ] are needed to define standardized measuring protocols and develop comparable irrigation procedures to improve the assessment of the different protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study are supportive of an overall general trend of suboptimal reporting practices in endodontic research, affecting even the most recent published reports, whilst being inbred also to the most rigorous study designs. Interestingly, only one fourth of randomized trials in Endodontics have been identified as pertaining to ‘high’ quality overall (Nagendrababu et al 2021a, b), whilst misinterpretation of research findings and distortion of results through reporting strategies have been identified both within endodontic research and also beyond (Eleftheriadi et al . 2020, Fang et al .…”
Section: Discussionmentioning
confidence: 99%
“…2020, Nagendrababu et al . 2021a, b). Apparently, the quality of the presentation of sample size reporting is of utmost significance and should be aligned to consider the specific outcome under evaluation, along with information on the effect size for which the specified power is attained.…”
Section: Introductionmentioning
confidence: 99%